Uterus Unicornis and Unilateral Ovarian and Renal Agenesis in A Case with Primary Amenorrhoea - Osmanağaoğlu, Mehmet; Güven, Süleyman; Aran, Turhan; Özgür, Mustafa; Vurallı, Barış; Görkem İlhan, Ceylan; Bozkaya, Hasan (Gynecology Obstetrics & Reproductive Medicine, 2010)
The purpose of this study is to report a case of primary amenorrhoea, uterus unicornis and unilateral ovarian and renal agenesis. A 17-year-old girl was referred to our university hospital because of primary amenorrhoea. Secondary sex characters were concordant with her age, hormonal tests were normal and the rectal examination identified a small uterus. An abdominopelvic ultrasound and pelvic magnetic resonance imaging were performed but could not detect uterus, endometrial line and both of the two ovaries. A chromosome karyotype analysis showed a normal 46, XX. A laparoscopy had confirmed the diagnosis of a unicornuate uterus with no evidence of a rudimentary horn and one tube, one round ligament and one normal ovary on the left side. Agenesis of the right kidney was found on postoperative intra venouse pyelography. Estradiol hemihydrate 2 mg estrogen orally once per day 21 days and after 10 mg medroxyprogesterone acetate was initiated for 3 months. Although their causes are controversial, they can be created by a localized defect at the caudal section of the Mullerian canal and genital ridge area or an adnexal torsion during intra-uterine period.